Commelina diffusa Population Dynamics in Banana and Ruderal Habitats under Mechanical and Herbicide Management Regimes - Wendy-Ann P. Isaac; Richard A. I. Brathwaite; Ayub Khan (International Journal of Agronomy)
Commelina diffusa is a colonising species of banana orchard habitats in St. Vincent in the Windward Islands of the Caribbean. In the present study, the population dynamics of C. diffusa were investigated in response to mechanical weed management with either a rotary string trimmer or glufosinate in ruderal and banana habitats. The study focused on density and size distribution of the weed over time and their response to two weed management strategies. The population dynamics of C. diffusa differed between the two habitats. Seedling establishment appeared to be an important factor influencing the dynamics of C. diffusa in banana orchards as there was little recruitment of seeds with less flower production compared with ruderal habitats where plants produced more flowers. Plants of C. diffusa in the banana orchard habitat had a longer growth cycle. In the banana orchard habitat, the C. diffusa population was greater and the plants were shorter with mechanical management than in areas treated with glufosinate. The results suggest that it is possible to manipulate the dynamics of C. diffusa in banana orchards as there is less chance of seed recruitment. Further research is necessary to refine an IPM approach for the management of C. diffusa.